AN ANALYSIS OF THE DYNAMICS OF FISCAL AND MONETARY POLICY IN BRAZIL AFTER THE IMPEACHMENT OF PRESIDENT DILMA ROUSSEFF - do Nascimento, Adriane Aparecida Barbosa; de Lima, Victor José Rocha (Seven Editora, 2025)
This study aims to analyze whether there was a regime of fiscal dominance in Brazil between September 2016 and December 2021, covering the Temer administration and the first three years of the Bolsonaro administration. Using an econometric methodology based on bivariate and multivariate Granger causality tests, the study examines the relationship between the interest rate, public debt, primary surplus, real exchange rate, and country risk. The results indicate that, during the analyzed period, the Brazilian economy was under a regime of monetary dominance, where fiscal policy did not impose significant constraints on monetary policy, and variations in the primary surplus were crucial in stabilizing the debt-to-GDP ratio. DOI: https://doi.org/10.56238/sevened2025.029-007